PEMBERDAYAAN PELAKU UMKM MELALUI PELATIHAN BRANDING DAN PEMASARAN DIGITAL BERBASIS EKONOMI KREATIF DI SANTORINI TALUMOLO - Novita Rolinsa Madina; Ria Anggita Zen (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program aimed to strengthen the capacity of Micro, Small, and Medium Enterprises (MSMEs) in business digitalization through training on branding, digital marketing, and creative economy-based product innovation. The program was conducted at Santorini Talumolo on March 16, 2026, involving 40 MSME participants. The methods included lectures, interactive discussions, hands-on assistance in creating digital content, and the development of online marketing strategies, with evaluation using a pretest-posttest design. The results demonstrated a significant improvement in participants’ understanding of digital branding strategies, the utilization of social media and online marketplaces, and the importance of product innovation in enhancing business competitiveness. The participants’ average score increased from 52.1 to 84.1 after the training. Overall, the program made a tangible contribution to local economic empowerment and promoted the sustainable digital transformation of MSMEs in the Santorini Talumolo area.